GROWTH TRENDS OF SUGARCANE (Saccharum officinarum) CROP IN ANDHRAPRADESH - K. SUPRIYA, R. GREESHMA, M.H.V. BHAVE and (The Journal of Research, PJTSAU, 2017)
Sugarcane (Saccharum officinarum) is the important commercial crop in the world. India ranks second in the World in sugarcane production after Brazil. In India, sugarcane occupies three per cent of the total cultivated area and shares about 7.5 percent of total value of agricultural output. Sugarcane is an efficient source of sugar, thus provides raw material for the second largest agrobased industry. In India during 2011-12 sugarcane was cultivated in an area of 50.38 lakh hectares with production of 361.04 million tonnes and with a productivity of 71.7 tonnes ha-1. In Andhra Pradesh during 2011-12, the area under sugarcane crop was 2.04 lakh hectares and production was 166.89 million tonnes with a productivity of 81.8 tonnes ha-1 (Source : Directorate of Economics and Statistics, 2012).